2013
DOI: 10.3109/01676830.2013.841716
|View full text |Cite
|
Sign up to set email alerts
|

Wegener Granulomatosis-associated Optic Perineuritis

Abstract: The morphological similarity and the anatomical continuity between the meningeal and the perioptic tissues suggest that extension of granulomatous inflammation along such tissue planes accounted for visual loss in these two patients with WG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 4 publications
1
35
0
Order By: Relevance
“…Retro-bulbar optic neuritis due to adjacent granulomatosis has been described (51). Takazawa reported optic perineuritis that caused by granulomatous infiltration in two patients (52). Both anterior ischemic optic neuropathy (AION) and posterior ischemic optic neuropathy (PION) have been described in patients with GPA secondary to vasculitis disrupting the blood supply to the optic nerve (31,53).…”
Section: Neuro-ophthalmicmentioning
confidence: 99%
“…Retro-bulbar optic neuritis due to adjacent granulomatosis has been described (51). Takazawa reported optic perineuritis that caused by granulomatous infiltration in two patients (52). Both anterior ischemic optic neuropathy (AION) and posterior ischemic optic neuropathy (PION) have been described in patients with GPA secondary to vasculitis disrupting the blood supply to the optic nerve (31,53).…”
Section: Neuro-ophthalmicmentioning
confidence: 99%
“…In terms of treatment, OPN with GPA responds to high-dose corticosteroid therapy very well, and the ophthalmological prognosis is mostly favorable in the short term. However, patients in whom high-dose corticosteroid treatment was delayed for a long period after the onset of symptoms experienced an irreversible loss of vision (2,4). High-dose corticosteroid therapy should therefore be administered as soon as possible after onset to minimize the possibility of vision loss.…”
Section: Discussionmentioning
confidence: 99%
“…Yoshitaka Kimura 1,2 , Kurumi Asako 1 After four years of maintenance therapy with PSL and MTX at the dosages indicated above, GPA recurred with an accompanying fever, headache, and exacerbated sinusitis. A chest computed tomography scan showed multiple lung nodules in the upper quadrant of the right lung.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In recent, OPN has generally been considered to represent a form of idiopathic inflammatory disease, 2 while OPN occasionally occurs as a manifestation of specific infectious or inflammatory disorders, such as Wegener's granulomatosis, sarcoidosis or syphilis. [3][4][5][6] The prognosis for visual outcome in OPN patients is generally good, but optic nerve atrophy after optic nerve sheath inflammation can occur and worsen the prognosis in some cases of OPN patients. 2 With the increasing use of optical coherence tomography (OCT), many researchers have observed that retinal nerve fiber layer thickness measured by OCT could be a good monitoring technique for quantifying axonal loss in optic neuropathy 7,8 Therefore, OCT findings might be useful diagnostic technique and prognostic indicator in various optic neuropathy.…”
Section: Introductionmentioning
confidence: 99%